Implicit Attitudes About Agricultural and Aquatic Products From Fukushima Depend on Where Consumers Reside - Tsegmed, Otgonchimeg; Taoka, Daiki; Qi, Jiang; Ariga, Atsunori (Frontiers in Psychology, 2019)
Japanese consumers are still hesitant to purchase products from Fukushima, although 7 years have passed since the Fukushima nuclear disaster and these products are officially considered safe. In this study, we examined whether Japanese consumers have negative implicit attitudes towards agricultural and aquatic products from the Fukushima region and whether these attitudes are independent of their explicit attitudes. Japanese students completed an implicit association test and a questionnaire to assess their implicit and explicit attitudes towards products from Fukushima relative to another region. The results of two experiments reliably demonstrated that the public has negative implicit attitudes towards Fukushima products, whereas their explicit attitudes are consistently positive. These observations predominantly held for participants living close to Fukushima (Tokyo) as opposed to participants living far away (Hiroshima): Experiment 1 (n = 40). Furthermore, individual differences in aversion to germs contributed to the implicit attitudes; the implicit negative attitudes were attenuated among the participants with a relatively low aversion to germs: Experiment 2 (n = 60). These results suggest that the implicit attitudes associated with the behavioral immune system, which is conceptualized as a suite of psychological mechanisms designed to proactively resist pathogenic threats, may underlie the hesitation to purchase products from Fukushima.